Reduction of Movement in Neurological Diseases: Effects on Neural Stem Cells Characteristics - Adami, Raffaella; Pagano, Jessica; Colombo, Michela; Platonova, Natalia; Recchia, Deborah; Chiaramonte, Raffaella; Bottinelli, Roberto; Canepari, Monica; Bottai, Daniele (Frontiers in Neuroscience, 2018)
Both astronauts and patients affected by chronic movement-limiting pathologies face impairment in muscle and/or brain performance. Increased patient survival expectations and the expected longer stays in space by astronauts may result in prolonged motor deprivation and consequent pathological effects. Severe movement limitation can influence not only the motor and metabolic systems but also the nervous system, altering neurogenesis and the interaction between motoneurons and muscle cells. Little information is yet available about the effect of prolonged muscle disuse on neural stem cells characteristics. Our in vitro study aims to fill this gap by focusing on the biological and molecular properties of neural stem cells (NSCs). Our analysis shows that NSCs derived from the SVZ of HU mice had shown a reduced proliferation capability and an altered cell cycle. Furthermore, NSCs obtained from HU animals present an incomplete differentiation/maturation. The overall results support the existence of a link between reduction of exercise and muscle disuse and metabolism in the brain and thus represent valuable new information that could clarify how circumstances such as the absence of load and the lack of movement that occurs in people with some neurological diseases, may affect the properties of NSCs and contribute to the negative manifestations of these conditions.